Post-migration experiences, cultural practices and homemaking : an ethnography of Dominican migration to Europe - Dinmohamed, Sabrina Seema, 1980- (Emerald Publishing Limited, 2023)
Homemaking studies have consistently demonstrated a lack of attention to different meanings of practices within immigrant groups, creating a biased picture which orients immigrants towards their country of origin when making home in the receiving society. Furthermore, their homemaking practices are mostly considered individualistically, without taking into account how the characteristics of the receiving society might influence homemaking. Proposing a more comprehensive approach, Post-Migration Experiences, Cultural Practices and Homemaking highlights immigrant stories and experiences that value cultural practices in making "home'. How, for example, is home created in a country like the Netherlands where the Dominican population is a small, almost invisible, community? Offering a broader perspective on immigrants' post-migration experiences, Sabrina Dinmohamed's approach substantially reconsiders traditional ideas about immigrant settlement and participation in receiving societies by analysing the individual and collective dimensions of homemaking practices in both public and private places. Moving away from questions of integration and towards immigrant stories and experiences on a micro level, Dinmohamed explores the meaning of food practices from the Dominican Republic in the process of homemaking by closely considering food consumption, preparation, ingredient sourcing, and other related customs. Shining a light on previously "invisible' immigrant communities, Post-Migration Experiences, Cultural Practices and Homemaking both advances knowledge about Caribbean migration to Europe, specifically within the Dominican diaspora, and explores how attention to feelings of home and cultural practices provides insights into immigrants' settlement experiences.
Keywords: Immigrants -- Europe -- Social life and customs.; Dominicans (Dominican Republic) -- Europe.; Home.; Dominican Republic -- Emigration and immigration.; Europe -- Emigration and immigration.; Social Science, Emigration & Immigration.; Migration, immigration & emigration.; elektronické knihy; electronic books